ICHTHYOFAUNAL DIVERSITY OF GANDIALI DAM, DISTRICT KOHAT, KHYBER PAKHTUNKHWA, PAKISTAN - Kalim Ullah; Atta Ullah; Rahat Farzeen (Journal Park Publishing, 2022)
Aim of our research work is concentrated on biodiversity of fishes of Gandiali Dam of district Kohat. A total of 20 Fish samples were collected from Gandiali Dam of district Kohat Khyber Pakhtunkhwa with the help of local fishermen. He used different types of nets namely hand net, cast net and hooks from January to May 2021. All the fishes were brought to the Laboratory of Zoology Government Post Graduate college Karak, small live fishes (upto 15 cm) were directly transferred to formalin solution and died on the spot (1 part formalin and 9 parts water or 10 ml formalin and 90 ml water), while large live fishes were transferred to this solution, fish died in this solution after dashing for a couple of minutes and usually at the time of death all the fins become fully expanded making possible to count the number of fin rays etc., making it easy for identification of many species. For preservation of large sized (from 15 to about 30 cm and above) specimen a narrow cut was made on the abdominal wall, concentrated formalin was also injected at several points along the abdominal region. Then each fish sample was identified up to species level. Identification of the species was made on the basis of their color pattern, specific spots or marks on the surface of the body, shape of the body, structure of various fins etc. A total of 7 species were reported during the sampling period, which belonged to two orders (Cypriniformes and Channiformes), two families (Cyprinidae and Channidae) and seven genera. Family Cyprinidae was the most abundant family with 6 species (19 samples) viz Cyprinus carpio, Labeo rohita, Ctenopharyngodon idella, Hypophathalmichthys molitrix, Carassius auratus and Puntius ticto. Family Channidae was represented by Channa punctatus (1 sample). During the sampling period, most abundant specie reported was Cyprinus carpio (08 samples) followed by Labeo rohita. The present study concludes with a note that the water bodies of Gandiali dam District Kohat, Khyber Pakhtunkhwa are home to rich and diverse fauna of cyprinids, and cyprinids have successfully adapted themselves to the haline water of the area. Further studies are required to evaluate the mechanism which enables those freshwater fishes survive and thrive in such extreme haline environment.
Keywords: Icthyo fauna; Diversity, Gandiali; Dam and Kohat